Incidence and predictors of interstitial lung disease (ILD) in Thai patients with early systemic sclerosis: Inception cohort study - Suparaporn Wangkaew (2018)
© 2015 Japan College of Rheumatology. Objectives: To determine and compare the prevalence of interstitial lung disease (ILD), the severity of high-resolution computed tomography (HRCT) score and incidence rate (IR) of ILD between the two subsets of early-SSc (systemic sclerosis) patients. We also determined the factors associated with ILD. Methods: We used an inception cohort of early-SSc patients seen between January 2010 and June 2014. All patients underwent HRCT at study entry and annually thereafter. Results: One hundred and thirteen patients (66 females and 89 diffuse cutaneous SSc [dcSSc]) with a mean ± SD age of 53.4 ± 8.4 years and mean disease duration of 12.9 ± 10.3 months at cohort entry were enrolled. At enrollment, patients with dcSSc had a higher prevalence of ILD (78.7% vs. 45.8%, p = 0.002), and a higher total HRCT score (10.3 ± 9.5 vs. 4.4 ± 5.6, p = 0.001) compared with limited cutaneous SSc (lcSSc). DcSSc patients had a higher IR of ILD than lcSSc patients (58.8 vs.17.3 per 100 person-years, p < 0.001). Univariable analysis revealed that male gender, presence of anti-Scl 70 and absent anti-centromere antibody was significant predictors of ILD. In Cox-regression analysis, a positive anti-centromere [hazard ratio (HR) 0.09 95% confidence interval (95% CI 0.01–0.73)] was a protective factor. Conclusions: DcSSc patients had more severe HRCT scores and higher IR of ILD compared with lcSSc patients. Male gender, presence of anti-Scl 70, and absent anti-centromere antibody predicted the future development of ILD in early-SSc patients.